Introduction: the image between presence and absence (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Dream images, anticipations of the future, memories of the past, perceptual distortions, delusional hallucinations, cognitions intoxicated by alcohol and drugs have always inhabited the visual representations of paintings, comics, films, television series, videogames and, more recently, virtual reality installations. We call them “altered states of consciousness”, meaning any perceptual state other than ordinary human perception
Keywords: Altered states; Hallucination; Immersive media; Filmic representation; Dream